Diversão e sobrevivência: sociabilidades em São José dos Campos (1930-1940) - Silva, Antonio Carlos Oliveira da (2009)
This dissertation has as its main objective the study of the language used by the press, the government papers and local memorialists on the behavior and sociabilities of the residents of the city of São Jose dos Campos, especially the poor and their circulation in public spaces, during the sanatorial period between 1930 and 1940. The residents in search of amusement still organized themselves in their own traditional ways. Due to new laws and public policies that were being implemented in the thirties, the local inhabitants found themselves coerced by the new political, economic and medical policies which tried to submit the poor of rural origins to new more civic and healthier behavior. The small town of São Jose survived of agriculture and raising of livestock. These local productions promoted intense trade between country and city. The merchants and business men along with local authorities tried to build an alternative urban way of life. They adopted strict orders against the popular places were the poor used to meet for drinking and gambling, considering these places dangerous and prone to violence and crimes. In this research we documented the tense relations between authorities and local people that stood up and resisted changes on their daily habits